Influence of insurance status on the postoperative outcomes of cytoreductive surgery and HIPEC. Issue 4 (5th December 2022) - Kubi, Boateng; Nudotor, Richard; Fackche, Nadege; Rowe, Julian; Cloyd, Jordan M.; Ahmed, Ahmed; Grotz, Travis E.; Fournier, Keith; Dineen, Sean; Veerapong, Jula; Baumgartner, Joel M.; Clarke, Callisia; et al.
Abstract: Background: Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is increasingly performed for peritoneal surface malignancies but remains associated with significant morbidity. Scant research is available regarding the impact of insurance status on postoperative outcomes. Methods: Patients undergoing CRS/HIPEC between 2000 and 2017 at 12 participating sites in the US HIPEC Collaborative were identified. Univariate and multivariate analyses were used to compare the baseline characteristics, operative variables, and postoperative outcomes of patients with government, private, or no insurance. Results: Among 2268 patients, 699 (30.8%) had government insurance, 1453 (64.0%) had private, and 116 (5.1%) were uninsured. Patients with government insurance were older, more likely to be non‐white, and comorbid ( p < 0.05). Patients with government (OR: 2.25, CI: 1.50−3.36, p < 0.001) and private (OR: 1.69, CI: 1.15−2.49, p = 0.008) insurance had an increased risk of complications on univariate analysis. There was no independent relationship on multivariate analysis. An American Society of Anesthesiologists score of 3 or 4, peritoneal carcinomatosis index score >15, completeness of cytoreduction score >1, and nonhome discharge were factors independently associated with a postoperative complication. Conclusion: While there were differences in postoperative outcomes between the three insurance groups on univariate analysis, there was no independent association between insurance status and postoperative complications after CRS/HIPEC.